Air purifiers that diffuse reactive oxygen species potentially cause DNA damage in the lung - Sato, Itaru; Kawamoto, Kosuke; Yoshida, Midori; Tsuda, Shuji (Journal of toxicological sciences, 2010)
Several appliance manufacturers have recently released new type air purifiers that can disinfect bacteria, fungi and viruses by diffusing reactive oxygen species (ROS) into the air. In this study, mice were exposed to the outlet air from each of 3 air purifiers from different manufacturers (A, B, C), and the lung was examined for DNA damage, lipid peroxidation and histopathology to confirm the safety of these air purifiers. Neither abnormal behavior during exposure nor gross abnormality at necropsy was observed. No histopathological changes were also observed in the lung. However, significant increase of DNA damage was detected by the comet assay in the lung immediately after the direct exposure for 48 hr to models A and B, and for 16 hr to model B. As for model B, DNA migration was also increased by 2 hr exposure in a 1 m3 plastic chamber but not by 48 hr exposure in a room (12.6 m3). Model C did not cause DNA damage. Lipid peroxidation and 8-hydroxy deoxyguanosine (8-OH-dG) was not increased under the conditions DNA damage was detected by the comet assay. The present results revealed that some models of air purifiers that diffuse ROS potentially cause DNA damage in the lung although the mechanism was left unsolved.